B cells in the balance: Offsetting self-reactivity avoidance with protection against foreign - Young, Clara; Lau, Angelica W. Y.; Burnett, Deborah L. (Frontiers in Immunology, 2022)
Antibodies are theoretically limitless in their diversity and specificity to foreign antigens; however they are constrained by the need to avoid binding to self. Germinal centers (GC) allow diversification and maturation of the antibody response towards the foreign antigen. While self-tolerance mechanisms controlling self-reactivity during B cell maturation are well recognized, the mechanisms by which GCs balance self-tolerance and foreign binding especially in the face of cross-reactivity between self and foreign, remain much less well defined. In this review we explore the extent to which GC self-tolerance restricts affinity maturation. We provide evidence that the outcome is situationally dependent, affected by affinity and avidity to self-antigen, and the extent to which self-binding and foreign-binding are interdependent. While auto-reactive GC B cells can mutate away from self while maturing towards the foreign antigen, if no mutational trajectories allow for self-reactive redemption, self-tolerance prevails and GC responses to the foreign pathogen are restricted, except when self-tolerance checkpoints are relaxed. Finally, we consider whether polyreactivity is subject to the same level of restriction in GC responses, especially if polyreactivity is linked to an increase in foreign protection, as occurs in certain broadly neutralizing antibodies. Overall, the outcomes for GC B cells that bind self-antigen can range from redemption, transient relaxation in self-tolerance or restriction of the antibody response to the foreign pathogen.